2020
DOI: 10.1088/1757-899x/902/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Cs-137 radionuclide bioaccumulation study in gold fish (Cyprinus carpio) through freshwater path with variations of potassium ion concentration (K+)

Abstract: Few anthropogenic radionuclides like Cs-137 are difficult to detect. It needs a method to evaluate the environment quality based on molecular network of an organism exposed to the radionuclide arises, and the said method is called Biomonitoring. In this study, biokinetic experiment is conducted with the determination of Concentration Factor (CF) and Bioaccumulation Factor values of Cs-137 in goldfish (Cyprinus carpio) by means of freshwater influenced by its aquatic environment condition, which is potassium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In salinity of 27 ppt, the highest CF va-lue is 3.16 mL.g -1 on the first day and 7.97 mL.g -1 on the last day. It demonstrated that the variability of cesium uptake at different salinities was primarily due to a change in ambient K + concentration (Ke et al, 2000;Baramanda et al, 2020). Generally, small increases in salinity and temperature increase the cesium uptake and biological activity (Prihatiningsih et al, 2016).…”
Section: Figure 5 Effect Of Salinity On the Constant Value Of Uptake And Elimination Of Znmentioning
confidence: 99%
“…In salinity of 27 ppt, the highest CF va-lue is 3.16 mL.g -1 on the first day and 7.97 mL.g -1 on the last day. It demonstrated that the variability of cesium uptake at different salinities was primarily due to a change in ambient K + concentration (Ke et al, 2000;Baramanda et al, 2020). Generally, small increases in salinity and temperature increase the cesium uptake and biological activity (Prihatiningsih et al, 2016).…”
Section: Figure 5 Effect Of Salinity On the Constant Value Of Uptake And Elimination Of Znmentioning
confidence: 99%
“…4 As a result of its nuclear properties, 137 Cs is the primary source of penetrating gamma radiation for decades aer discharge of, e.g., spent nuclear fuel. 5,6 Similar to the other alkali metals, cesium is water-soluble and prone to bioaccumulation in marine and freshwater ecosystems due to its capability of substituting sodium and potassium in living organisms [7][8][9][10] . Ingestion of 137 Cs leads to the accumulation of this radioactive isotope in so tissues from the thyroid, lungs, breast, and bone marrow, [11][12][13][14] resulting in a biological action similar to a continuous exposure to radiation from external sources.…”
Section: Introductionmentioning
confidence: 99%
“…The study of bioaccumulation of radionuclides and other contaminants that is based on aquaria experiments is still limited. The biokinetic study was reported for the bioaccumulation of 137 Cs by Chanos Chanos and by Cyprinus carpio [9][10]. The study of bioaccumulation of chloramphenicol by Paneous monodon and heavy metal by Perna Viridis has been reported [11][12].…”
Section: ■ Introductionmentioning
confidence: 99%